Optimal. Leaf size=27 \[ e^2 \left (-1+e^{e^{e+x (3+x)}+x}-\frac {x}{-1+x}\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.50, antiderivative size = 26, normalized size of antiderivative = 0.96, number of steps used = 5, number of rules used = 4, integrand size = 70, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.057, Rules used = {27, 6688, 12, 6706} \begin {gather*} e^{x+e^{x (x+3)+e}+2}+\frac {e^2}{1-x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 27
Rule 6688
Rule 6706
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^2+e^{e^{e+3 x+x^2}+x} \left (e^2 \left (1-2 x+x^2\right )+e^{2+e+3 x+x^2} \left (3-4 x-x^2+2 x^3\right )\right )}{(-1+x)^2} \, dx\\ &=\int e^2 \left (\frac {1}{(-1+x)^2}+e^{e^{e+x (3+x)}+x} \left (1+e^{e+x (3+x)} (3+2 x)\right )\right ) \, dx\\ &=e^2 \int \left (\frac {1}{(-1+x)^2}+e^{e^{e+x (3+x)}+x} \left (1+e^{e+x (3+x)} (3+2 x)\right )\right ) \, dx\\ &=\frac {e^2}{1-x}+e^2 \int e^{e^{e+x (3+x)}+x} \left (1+e^{e+x (3+x)} (3+2 x)\right ) \, dx\\ &=e^{2+e^{e+x (3+x)}+x}+\frac {e^2}{1-x}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.33, size = 26, normalized size = 0.96 \begin {gather*} e^2 \left (e^{e^{e+3 x+x^2}+x}-\frac {1}{-1+x}\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.63, size = 37, normalized size = 1.37 \begin {gather*} \frac {{\left (x - 1\right )} e^{\left ({\left (x e^{2} + e^{\left (x^{2} + 3 \, x + e + 2\right )}\right )} e^{\left (-2\right )} + 2\right )} - e^{2}}{x - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.23, size = 43, normalized size = 1.59 \begin {gather*} \frac {x e^{\left (x + e^{\left (x^{2} + 3 \, x + e\right )} + 2\right )} - e^{2} - e^{\left (x + e^{\left (x^{2} + 3 \, x + e\right )} + 2\right )}}{x - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.28, size = 25, normalized size = 0.93
method | result | size |
risch | \(-\frac {{\mathrm e}^{2}}{x -1}+{\mathrm e}^{2+{\mathrm e}^{{\mathrm e}+x^{2}+3 x}+x}\) | \(25\) |
norman | \(\frac {{\mathrm e}^{2} x \,{\mathrm e}^{{\mathrm e}^{{\mathrm e}+x^{2}+3 x}+x}-{\mathrm e}^{2} {\mathrm e}^{{\mathrm e}^{{\mathrm e}+x^{2}+3 x}+x}-{\mathrm e}^{2}}{x -1}\) | \(46\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.45, size = 24, normalized size = 0.89 \begin {gather*} -\frac {e^{2}}{x - 1} + e^{\left (x + e^{\left (x^{2} + 3 \, x + e\right )} + 2\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.31, size = 28, normalized size = 1.04 \begin {gather*} {\mathrm {e}}^{{\mathrm {e}}^{3\,x}\,{\mathrm {e}}^{x^2}\,{\mathrm {e}}^{\mathrm {e}}}\,{\mathrm {e}}^2\,{\mathrm {e}}^x-\frac {{\mathrm {e}}^2}{x-1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.48, size = 24, normalized size = 0.89 \begin {gather*} e^{2} e^{x + e^{x^{2} + 3 x + e}} - \frac {e^{2}}{x - 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________